Impact of lymph node ratio on survival and recurrence outcomes in oral squamous cell carcinoma. Issue 10 (October 2022) - Mamic, M.; Lucijanic, M.; Lorencin, M.; Suton, P.; Luksic, I.
Abstract: Growing evidence supports the lymph node ratio (LNR) as a prognostic factor for survival in patients with oral squamous cell carcinoma (OSCC). However, there is a lack of data regarding its association with recurrence outcomes. Data on 163 patients with OSCC who underwent primary surgical treatment at a tertiary centre between January 2009 and December 2015 were collected retrospectively and analysed. Receiver operating characteristic curve analysis was performed to determine optimal cut-off values for the survival analyses. Survival endpoints were disease progression/relapse for disease-free time (DFT), freedom from loco-regional recurrence (FLR), and freedom from distant metastasis (FDM), and as death from any cause for overall survival (OS). Patients with a lower LNR were found to have significantly superior DFT (LNR < 14%, P < 0.001), FLR (LNR <14%, P < 0.001), FDM (LNR <16%, P = 0.004), and OS (LNR <7%, P = 0.004) in comparison to patients with a higher LNR. LNR is a good predictor of survival and recurrence outcomes in OSCC.